Evaluation of a new upper body ergometer for cross-country skiers - Wisloff, U.; Helgerud, J. (Medicine & Science in Sports & Exercise, 1998)
A new specific ski ergometer has been developed to study aerobic endurance and force development in the upper body of cross-country skiers. The major purpose of the present study was to examine the validity and the reliability of this ergometer. The study showed the ski ergometer to be both reliable and valid for evaluating VO2 and force development in the upper body at submaximal and maximal workloads for cross-country skiers.